2022
DOI: 10.1371/journal.pone.0262760
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fetal growth in Africa: Application of the international WHO and INTERGROWTH-21st standards in a Beninese pregnancy cohort

Abstract: Background Fetal growth restriction is a major complication of pregnancy and is associated with stillbirth, infant death and child morbidity. Ultrasound monitoring of pregnancy is becoming more common in Africa for fetal growth monitoring in clinical care and research, but many countries have no national growth charts. We evaluated the new international fetal growth standards from INTERGROWTH-21st and WHO in a cohort from southern Benin. Methods Repeated ultrasound and clinical data were collected in women f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Moreover, the coefficients for the WHO fetal growth charts with a ReadMe‐pdf was made available online in March 2023: https://github.com/jcarvalho45/WhoFetalGrowth. Finally, the results in France were consistent with those of many international studies that have shown better detection of SGA fetuses with WHO and Hadlock's charts compared with Intergrowth 22–26 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the coefficients for the WHO fetal growth charts with a ReadMe‐pdf was made available online in March 2023: https://github.com/jcarvalho45/WhoFetalGrowth. Finally, the results in France were consistent with those of many international studies that have shown better detection of SGA fetuses with WHO and Hadlock's charts compared with Intergrowth 22–26 …”
Section: Discussionsupporting
confidence: 88%
“…Finally, the results in France were consistent with those of many international studies that have shown better detection of SGA fetuses with WHO and Hadlock's charts compared with Intergrowth. [22][23][24][25][26] The strength of our approach is the comparison of charts using multiple data sources to synthesize the evidence supporting the choice of a chart. In addition, the studies used large samples of French births with data abstracted from medical records on ultrasound measurements which are well-standardized in France according to national guidelines.…”
Section: Discussionmentioning
confidence: 99%